Magnetic and transport properties of La0.7Sr0.3MnO3/Pr0.65Ca0.35MnO3 multilayered films with different microstructure - Prokhorov, V.G.; Flis, V.S.; Kaminsky, G.G.; Lee, Y.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
The magnetic and transport properties of single-crystal and polycrystalline La0.7Sr0.3MnO3/Pr0.65Ca0.35MnO3 multilayered films are investigated in the temperature range 4.2–300 K. It is shown that the transformation from an incoherent to a coherent interface between layers leads to an enhancement of the ferromagnetic coupling, which is accompanied by a modification in the temperature dependence of the resistance and by a grown negative magnetoresistance ratio at room temperature. The influence of grain boundaries on the transport of carriers in the multilayered films is discussed on the basis of modern theoretical approaches.